Patterns and Determinants of Change in Cortisol Levels and Thyroid Function as a Function of Cardiac Risk in Children Undergoing Cardiac Surgery - Khouloud Abdulrahman Al-Sofyani; Mohammed Shahab Uddin; Ebtehal Ahmed Qulisy; Osman Osama Al-Radi (International Journal of Pediatrics)
Background. Children undergoing cardiac surgery with cardiopulmonary bypass (CPB) are exposed to the risk of hormonal imbalances resulting from acute stress, which may eventually result in high postoperative mortality and morbidity. Objective. We assessed adrenal and thyroid hormonal changes and their determinants following cardiac surgery in children and explored their prognostic value in predicting cardiac outcomes. Study Design and Methods. A prospective cohort study was conducted at King Abdulaziz University Hospital (KAUH), between 2017 and 2018. The study involved 46 children aged 14 years or younger who underwent elective cardiac surgery with cardiopulmonary bypass. Serum levels of cortisol, TSH, fT3, and fT4 were measured preoperatively and 24, 48, and 72 hours after surgery. The cardiac risk was assessed using the risk adjustment for congenital heart surgery (RACHS) scale. A composite cardiovascular outcome was analyzed as a numerical variable and calculated as the number of cardiovascular events. Results. Overall, the changes in thyroid function parameters resulted in a U-shaped curve, while cortisol levels yielded a bell-shaped curve. The most significant changes occurred at 24 hours postop, including a decrease in mean TSH by 2.08 μIU/L (p<0.001), fT3 by 2.39 pmol/L (p<0.001), and fT4 by 2.45 pmol/L (p<0.001) and an increase in cortisol levels by 406.48 nmol/L (p<0.001) with respect to the baseline. Cortisol concentration peaked higher and recovered slower among patients with high cardiac risk than their counterparts. Cardiovascular outcomes were independently predicted by the extent of the decline in fT4 and TSH at 48 and 72 hours postop, with reference to the baseline, and by the cortisol level at 24 h postop, independent of the baseline, besides the RACHS category. Conclusion. Cardiac surgery among children yields a high adrenocortical response and a high incidence of nonthyroidal illness syndrome, increasing cardiovascular risk. A preventive management strategy involves improving surgical techniques to minimize trauma-related stress.